The Investigation of Haplotype Phasing Efficiency at the PAH Gene Region in Iranian Family Trios - Z Fazeli; S Vallian (Tehran University of Medical Sciences, 2009)
Background: The haplotype phasing is more useful than genotyping markers independently at carrier detection and prenatal diagnosis of diseases. The PAH gene region contains several markers used in detection of PKU disease. In the present study, the efficiency of BglII-EcoRI-VNTR haplotype phasing in Iranian family trios was investigated. Then, this information was compared with those obtained for unrelated individuals. Methods: Blood samples were collected from 20 healthy family trios and 60 unrelated individuals. The genomic DNA was extracted by use of salting-out procedure. The two markers BglII and EcoRI were genotyped by use of PCR-RFLP. The genotype of VNTR marker was identified by use of PCR and electrophoresis. The genotyping data obtained from family trios was used to infer haplotype phase. We also compared this data with results obtained from a widely used method for haplotype frequency inference from unrelated individuals, the PHASE program. Results: The haplotype phase of all members was only ascertained at eight family trios.  The comparison of this data with the results obtained by use of PHASE program showed that eight haplotypes [211, 221, 215, 216, 214, 121, 225 and 111] were informative haplotypes in Iranian population. Conclusion: Since diversity of BglII-EcoRI-VNTR haplotypes was high in Iranian population, haplotype phasing at family trios was difficult. The results of this study showed that the genotyping data obtained from family trios could not provide enough information for BglII-EcoRI-VNTR haplotype phasing at Iranian PKU families and the genotyping of other family members was necessary at most cases.